Uses of geographic information systems to analyze the Hydro-Geotechnical hazards and related risks in the Tiflet watershed, Morocco - Chekkouch Hajar; Benammi Mohamed; Chakiri Saïd (E3S Web of Conferences)
Geographical information systems have a very important role in visualizing geographical, geological, hydrological and geotechnical data, in the form of layers in thematic maps that are easy to analyse and interpret on a local or regional scale. Based on multi-source and technical data, we have defined all the hydro-geotechnical hazards existing in the Oued Tiflet watershed. The latter is characterized by different lithological formations whose physical-mechanical parameters vary from upstream to downstream. By combining these characteristics with morphological and hydrological data, we can assess the degree of soil erodibility and identify unstable zones in each part of the watershed. And to provide a detailed geotechnical zoning of the Tiflet basin useful for future urbanization projects and the construction of engineering structures.